Demographic dynamics and art engagement: urban development in Lubbock and El Paso, Texas - Mehan, Asma; Alikhani, Sadaf (Estoa. Journal of the Faculty of Architecture and Urbanism, 2025)
Cities serve as dynamic arenas where citizens negotiate needs and co-create solutions to enhance urban life. To address the complexities of contemporary urban living, planning must respond to social justice, economic vitality, and cultural inclusion. This study explores how demographic factors—age, ethnicity, and economics—influence art engagement in two culturally distinct Texan cities: Lubbock and El Paso. Using qualitative comparative analysis and data from a graduate seminar at Texas Tech University, we examine student-led art projects reflecting community experiences. These creative works reveal how art fosters communication, cultural belonging, and social cohesion. Findings underscore that integrating art into urban planning—through public installations, murals, and participatory design—can revitalize underutilized spaces and address diverse community needs. The study argues for art as a tool of creative placemaking, especially in demographically varied cities, emphasizing that culturally responsive engagement strategies can cultivate inclusive, vibrant urban environments.